Adaptive S-Method for SAR/ISAR Imaging. (17th December 2007) - Stanković Stanković, LJubiša LJubiša; Thayaparan Thayaparan, Thayananthan Thayananthan; Popović Popović, Vesna Vesna; Djurović Djurović, Igor Igor; Daković Daković, Miloš Miloš
Abstract : We propose the adaptive S-method-based technique for imaging of SAR and ISAR targets. This approach can be applied in the 1D and 2D modes. It is a postprocessing technique, since the first stage is the standard radar imaging with the 2D Fourier transform. In addition, selection of the adaptive parameter in this technique is efficient and can be performed based on simple rules in real time. The proposed technique produces highly concentrated (focused) radar image without interferences commonly associated with time-frequency representations and without defocusing target images that are already focused in the 2D Fourier domain.